Block strength training improves functional autonomy and quality of life in community-dwelling older women - Sergio Galdames Maliqueo; Álvaro Huerta Ojeda; Emilio Jofré-Saldía; Hernaldo Carrasco-Beltrán; Mercedes-Mercedes Yeomans-Cabrera; Maximiliano Bravo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Block strength training has been proposed as a useful and practical strategy to reverse the effects of aging in community-dwelling older adults. However, the effects of block strength training based on the nature of exertion on functional autonomy and life quality of older women living in the community are unknown.